(untitled) (Proceedings of The National Conference on Community Engagement, 2026)
Household waste management remains a significant challenge in urban areas, including Ngletih Village, Pesantren District, Kediri City. Low public awareness of waste sorting and the absence of effective community-based waste management institutions contribute to increasing waste accumulation. This community service activity, conducted through the Community Service Program (KKN), aims to empower the community by strengthening and establishing a waste bank as a sustainable waste management initiative. The methods applied include socialization and training on waste management, establishment of a waste bank organizational structure, member recruitment, mapping of operational locations, and preparation of an implementation and initial mentoring plan. The results indicate an improvement in community awareness and participation in waste sorting, the formation of a structured waste bank organization, and the availability of an initial operational mechanism. This program is expected to serve as a foundation for sustainable community-based waste management while providing additional economic value for local residents.